Mathematical analysis of the flow and heat transfer of Ag-Cu hybrid nanofluid over a stretching/shrinking surface with convective boundary condition and viscous dissipation - Rahimah, Jusoh; K., Naganthran; A., Jamaludin; M. H., Ariff; M. F. M., Basir; I., Pop (Penerbit UMP, 2020)
Hybrid nanofluid has a vast potential of applications in the cooling system due to the high thermal conductivity. This study emphasizes on the impact of the convective boundary condition and viscous dissipation to the heat transfer of Ag-Cu hybrid nanofluid. A suitable similarity transformation is used to transform the partial differential equations of mass, momentum and energy into the ordinary differential equations. A finite difference code known as bvp4c in Matlab is employed to generate the numerical solutions. Stability analysis is conducted since dual solutions are generated in this study and the first solution exhibits the stability properties. The influence of variations in the suction parameter, viscous dissipation, nanoparticles concentration and Biot number on the on the temperature and velocity profiles of the hybrid nanofluid are portrayed. The rate of heat transfer is prominently higher with the augmentation of the Biot number and Ag nanoparticles concentration.